Aspects of dimensional deictic adverbs in the Ashéninka language of Alto Perené - Solari Ruiz-Eldredge, Oscar Augusto (2021)
In this research, we present the linguistic and pragmatic analysis of dimensional deictic adverbs used in the Ashéninka language of Alto Perené. Data were collected between 2014 and 2018 in three native Ashéninka communities located in the province of Chanchamayo (Junín). Among the grammatical manifestations of spatial deixis in the Ashéninka language we find those expressed through adverbs that describe situations oriented towards the position of the sender and the referent. In order to do so, this language has adverbs that systematize the positional notions of superiorityinferiority such as tonkari and otapina, as far as position is concerned, and jenoki and osabiki, as far as direction is concerned. Likewise, the notion of posteriority is systematized by means of otapiki and that of laterality by means of akopero and ampate. In most contexts, these adverbs attach the locative suffix <-ki> to obtain the category of deictic.